Meeting Venus: A Collection of Papers Presented at the Venus Transit Conference Tromsø 2012 - Aspaas, Per Pippin; Sterken, Christiaan (C. Sterken, Vrije Universiteit Brussel, 2013)
On 2–3 June 2012, the University of Tromsø hosted a conference about the cultural and scientific history of the transits of Venus. The conference took place in Tromsø for two very specific reasons. First and foremost, the last transit of Venus of this century lent itself to be observed on the disc of the Midnight Sun in this part of Europe during the night of 5 to 6 June 2012. Second, several Venus transit expeditions in this region were central in the global enterprise of measuring the scale of the solar system in the eighteenth century. The site of the conference was the Nordnorsk Vitensenter (Science Centre of Northern Norway), which is located at the campus of the University of Tromsø. After the conference, participants were invited to either stay in Tromsø until the midnight of 5–6 June, or take part in a Venus transit voyage in Finnmark, during which the historical sites Vardø, Hammerfest, and the North Cape were to be visited. The post-conference program culminated with the participants observing the transit of Venus in or near Tromsø, Vardø and even from a plane near Alta. These Proceedings contain a selection of the lectures delivered on 2–3 June 2012, and also a narrative description of the transit viewing from Tromsø, Vardø and Alta. The title of the book, Meeting Venus, refers to the title of a play by the Hungarian film director, screenwriter and opera director István Szabó (1938–). The autobiographical movie Meeting Venus (1991) directed by him is based on his experience directing Tannhäuser at the Paris Opera in 1984. The movie brings the story of an imaginary international opera company that encounters a never ending series of difficulties and pitfalls that symbolize the challenges of any multicultural and international endeavor. As is evident from the many papers presented in this book, Meeting Venus not only contains the epic tales of the transits of the seventeenth, eighteenth and nineteenth centuries, it also covers the conference participants’ encounter with “Venus on the Sun” in historical ...